1984
DOI: 10.1093/oxfordjournals.aje.a113921
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Depressive Symptoms Among Mexican Americans and Anglos

Abstract: The study reports epidemiologic field survey data on the distribution of depressive symptoms among Anglos (n = 637) and two Mexican-American subsamples (n = 551) living in Santa Clara County, California. One of the Mexican-American subsamples was interviewed in English (n = 330) and the other in Spanish (n = 221). Analysis of variance indicated that those with low educational achievement, females, those in disrupted marital statuses, and those under 30 years of age had significantly higher levels of depressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(32 citation statements)
references
References 0 publications
2
29
1
Order By: Relevance
“…Some studies have shown minimal differences among ethnic groups with regard to depression, 21 whereas other studies have found depression to be more prevalent among African American adolescents than other adolescents, 8 and still others have found it to be less prevalent among African American youths. 22 Data on depression among Hispanic youths have been mixed, 23,24 and previous research on Asian American adolescents has shown that Asian American adolescents are at a high risk for depression. Given the variability in results, these questions warrant further research.…”
Section: Commentmentioning
confidence: 99%
“…Some studies have shown minimal differences among ethnic groups with regard to depression, 21 whereas other studies have found depression to be more prevalent among African American adolescents than other adolescents, 8 and still others have found it to be less prevalent among African American youths. 22 Data on depression among Hispanic youths have been mixed, 23,24 and previous research on Asian American adolescents has shown that Asian American adolescents are at a high risk for depression. Given the variability in results, these questions warrant further research.…”
Section: Commentmentioning
confidence: 99%
“…Some studies have explored how psychological distress, depression, or other indicators ofmental health relate to acculturation in Hispanics; however, the results ofthese studies are inconsistent, with no clear indication ofthe direction ofthe association. [7][8][9][10][11][12][13][14][15] The biethnic population studied in the San Luis Valley Diabetes Study provided a unique opportunity to examine the relationship between quality of life and non-insulindependent diabetes mellitus (NIDDM) in Hispanic and non-Hispanic White subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kandel et al (1985) demonstrated that more educated women in New York City were less likely to experience depression than their less educated peers. Vega et al (1984) found identical results among Anglos and both English-and Spanish-speaking Chicanos in a California county.…”
Section: Structural Factors and Psychological Distressmentioning
confidence: 52%
“…For example, Radloff (1975) reported that women less than 25 years of age were more likely to experience depression than older women. In addition, Vega et al (1984) observed a negative relationship between age and psychological distress among Anglos and Chicanos in a California county, although this association was only significant for the former group. Similarly, Ross et al (1983c) found that older individuals were less likely to experience psychological distress than their younger neighbors in the El Paso/Ciudad Juarez area.…”
Section: Structural Factors and Psychological Distressmentioning
confidence: 87%
See 1 more Smart Citation